STRUKTUR DAN DISTRIBUSI PENDAPATAN SERTA TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI UBI KAYU DI KABUPATEN LAMPUNG TENGAH - Rosi Triafni Nurhayati; Raden Hanung Ismono; Yaktiworo Indriani (Lampung University, 2021)
This research aimed to analyze the difference of the income structure, the income distribution, and the welfare level of cassava farmer households based on factory location distance from location of cassava farm in Lampung Tengah Regency. The research sample consisted of 42 cassava farmers in Terusan Nunyai Subdistrict and 31 cassava farmers in Bandar Mataram Subdistrict. The data were analyzed using income structure, income distribution, and welfare level analysis based on BPS criteria. The results of this research showed that there was difference in the income structure between cassava farmers in Terusan Nunyai Subdistrict and Bandar Mataram Subdistrict. The income structure of cassava farmers had the highest contribution of the household income from main on-farm income which was 65.75 percent and 78.88 percent. There was also difference in the income distribution between cassava farmer households in Terusan Nunyai Subdistrict and Bandar Mataram Subdistrict. The income distribution of cassava farmer households in Terusan Nunyai Subdistrict was categorized as moderate inequality, welfare in Bandar Mataram Subdistrict was categorized as high inequality. There was no significant difference of the welfare level of cassava farmer households between the two locations. Based on BPS criteria, the welfare level of cassava farmer households in Terusan Nunyai and Bandar Mataram Subdistrict were categorized as prosperous farmer households.Key words: cassava, farmers, income, welfare